PENGARUH REMEDIAL TEACHING METODE TUTOR SEBAYA TERHADAP HASIL BELAJAR SISWA PADA MATERI STRUKTUR ATOM KELAS XI IPA SMA NEGERI 1 SANGGAU - Vivian Ardilah Dewi; Dedeh Kurniasih; Fitriani Fitriani (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTThis study aimed at finding out not only the difference of students’ learning outcomes taught by using peer tutor remedial teaching method and lecturing remedial teaching method on Atomic Structure class at grade XI IPA SMA Negeri I Sanggau but also the influence of the peer tutor remedial teaching methodon Atomic Structure class. Using quasi experimental and Nonequivalent Control Group Designs, this study employed 2 classes as the samples; grade XI IPA 2 class as the experiment group and grade XI IPA I class as the control group. The data collection technique used were measurement, observation, interview, and documentation. While the instruments used were Atomic Structure essay test and remedial test. The results of U Mann Whitneydata analysis  obtained  level of 5%, and probability score of Pvalue (0,043) < (0,05), so that the Ho was rejected dan and the Ha was accepted. In other words, there were significant differences of experiment and control groups. It could be seen from the Effect Size (ES) count of 0,66which considered in average category and Z table which indicated the significant effect to the students’ learning achievement (24,54%) to learning outcomes.Keywords: Remedial Teaching, Peer Tutor Method and Learning Outcomes